Pembangunan Jaringan Local Area Network SMK Negeri 1 Sragen - Susilo, Indrat (Speed - Sentra Penelitian Engineering dan Edukasi)
Admnistrative system plays an important role in the advancement of a school, with oc administration, of course, the school was said to have developed, but with less then administration would hinder the progress of a school. Thatâs what faced Vocational High School SMK NegeriÂ  1 Sragen today. Administration of the existing system is deemed notÂ  the needs of the existing administration. Many obstacles - obstacles encountered in ripieting the schoÃ¸l administration such as: Difficult to find data or files when the data files are needed immediately. This is caused by a computerized system based on the exsting administration in Vocational High School (SMK) 1 Sragen felt still less, still stand r their own computer or stand alone. To overcome this proposed solution is the Donstruction of the network, so that existing computers can communicate with each other so that both data and file sharing easier. The goals of ease in sharing files, data and information and savings in the use softwer or printer.There are several methods used in the execution of this Work Practice, among others: that is the herd book study method, read and understand a variety of books related to computer networks, methods of observation or observation that is held in place of internship direct observation of Vocational High School (SMK) 1 Sragen. Results from the constwction of this network is the easy exchange of data and information so that work can be completed quickly, precisely and accurately without the need for a long time.